The Implementation of Cloud Accounting in Indonesia: A Bibliometric Analysis - Molina; Dhieka Avrilia Lantana; Erwin Indriyanto; Kumba Digdowiseiso; Zalailah Salleh (CV ODIS, 2023)
This research adopts a bibliometric analysis approach to investigate the development of Cloud Accounting implementation in Indonesia in the 2018-2023 time period. Data was obtained via Google Scholar using keywords related to